2018
DOI: 10.1186/s41240-018-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-2 and MMP-9 activities by solvent-partitioned Sargassum horneri extracts

Abstract: Background: Matrix metalloproteinases (MMPs) are linked with several complications such as metastasis of cancer progression, oxidative stress, and hepatic fibrosis. Brown seaweeds are being extensively studied for their bioactive molecule content against cancer progression. In this context, Sargassum horneri was reported to possess various bioactivities including antiviral, antimicrobial, and anti-inflammatory partly due to its phenolic compound content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
See 1 more Smart Citation
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
“…wightii were effective in inhibiting the COX-2 enzyme activity. Several other compounds that are allegedly responsible for the anti-inflammatory activity of the non-polar fraction include fucoxanthin or its derivatives [33], fucosterol or other steroid compounds [20,23,28,29,31,33,51], and phenolic compounds [18,23,30,31,33]. Although phenolic compounds are commonly known to have hydrophilic natures, their polarities will actually depend on their chemical structures.…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentsmentioning
confidence: 99%
“…Results of this study proved a significant suppression of MMP-2 and MMP-9 level by CA with Cal treatment compared to CA and Cal alone treated cells. In the previous report [ 33 ], they observed that SHE inhibited both MMP activity and was illustrated as a ratio to that of activation of MMP-2 from pro-MMP-2. This reflects the regulatory dynamic between MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies on Sargassum summarized by Saraswati et al [ 6 ] indicated the promising anti-inflammatory effect of this seaweed genus, for both acute and chronic conditions. Although several screening studies demonstrated the predominance of Sargassum lipid-soluble fractions which are responsible for inflammatory activity [ 7 , 8 , 9 , 10 ], the potency of the lipid-soluble compounds of tropical Sargassum has not been fully explored. To date of our knowledge, the sulfated polysaccharides of tropical Sargassum are the most studied compounds for their anti-inflammatory activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%